APRESIASI MASYARAKAT TERHADAP MAKANAN DAN MINUMAN KAKI LIMA (STUDI KASUS MASYARAKAT DI SURAKARTA) - Nani Irma Susanti; Erna Tiningrum (STIE AUB Surakarta, 2013)
Foodandbeverages soldby PKL(street vendors) was onecontributor toa regionaleconomicturnaround. Although thebusinessunitwas smallbutwouldbe collectedwhenthe street vendorshada high valuefor the development ofregional.The data usedin this studywereprimary data takenwith a list ofquestions providedto the communityas asampleof 100 respondents.Testinstrumentanalyzingused, AnalysisRegression, t test, F test, testR2, and classical assumptionInstrumenttest resultsshowedallthe datawere valid and reliable. OfVariableRegressionanalysisSocial, Personaland Psychologicalshoweda positive influence onthe purchase decisionvariables. Variables thatmoststronglyinfluencedthepurchase decisionFoodandBeverageStreetinSurakartawasprivatevariable. Culturalvariableswhilenegativeaffect.Of thet testconcludedthat thevariableSocial, Personaland Psychologicalpositive and significant impactonFoodandBeveragePurchasingDecisionsStreetinSurakarta. Culturalvariableshad an influencewhile thenegativeandnot significant to theFoodandBeveragePurchasing DecisionsStreetinSurakarta. Keywords: Cultural, Social, andPsychologicalPersonalPurchase Decision